Performance evaluation of designated containerization and virtualization solutions using a synthetic benchmark - Sebastian Tarasiuk; Damian Traczuk; Kacper Szczepaniuk; Patryk Stoń; Jakub Smołka (Journal of Computer Sciences Institute)
The aim of this paper is the analysis of the performance of virtualization and containerization technologies in the context of IT infrastructure. The following virtualization technologies were selected for the study: VirtualBox, VMware and QEMU, as well as containerization technologies: Docker, Podman and LXD. In addition, microVM technologies such as QEMU and Firecracker, which are increasingly important in the context of virtualization, were also included. The comparative criteria on which the analysis is based include aspects of computing and memory performance. Tests conducted on selected technologies included testing CPU performance, RAM efficiency and disk speed for reading and writing data. A SysBench, synthetic benchmark, was used to conduct the tests.